An expert consensus to standardize acupuncture treatment for knee osteoarthritis. Issue 5 (October 2020) - Sun, Ning; Wang, Li-Qiong; Shao, Jia-Kai; Zhang, Na; Zhou, Ping; Fang, Sai-Nan; Chen, Wei; Yang, Jing-Wen; Liu, Cun-Zhi
Background: Acupuncture has been advocated for as a potentially effective therapy for patients with knee osteoarthritis (KOA) in systematic reviews and guidelines. However, there is still a lack of agreement on the optimal therapeutic protocol for acupuncture. This aim of this study was to develop an expert consensus regarding the therapeutic protocol of acupuncture to guide doctors in clinical practice. Methods: An initial list of items was based on an overview of research evidence from four databases and clinical problem investigation with a multidisciplinary panel. A two-step process was used to optimize the list, including semi-structured interviews with three acupuncture clinical experts and a three-round Delphi consensus survey with the voting panel. A nine-point Likert-type scale (1 = strongly disagree, 9 = strongly agree) was used to measure agreement. Results: In total, 52 professionals (response rate: 52%) confirmed their participation in the voting panel. The initial list including 28 items was evaluated. Following a three-round Delphi survey, a consensus was achieved including 37 items that can be broadly categorized into six domains: (1) main treatment principles, (2) acupuncture treatment, (3) dose of acupuncture intervention, (4) primary outcomes, (5) adverse events and (6) others. Conclusion: This expert consensus could be used to guide doctors in clinical practice and help patients with KOA gain access to appropriate and coordinated acupuncture treatment.